Respuesta :
Answer:
n = 5
Step-by-step explanation:
Step 1 :
Step 2 :
Pulling out like terms :
2.1 Pull out like factors :
-4n + 30 = -2 • (2n - 15)
Equation at the end of step 2 :
(0 - -6 • (2n - 15)) - -30 = 0
Step 3 :
Step 4 :
Pulling out like terms :
4.1 Pull out like factors :
12n - 60 = 12 • (n - 5)
Equation at the end of step 4 :
12 • (n - 5) = 0
Step 5 :
Equations which are never true :
5.1 Solve : 12 = 0
This equation has no solution.
A a non-zero constant never equals zero.
Solving a Single Variable Equation :
5.2 Solve : n-5 = 0
Add 5 to both sides of the equation :
n = 5
One solution was found :
n = 5
Processing ends successfully
plz mark me as brainliest :)
To solve this, you need to isolate/get the variable "n" by itself in the equation:
-3(-4n + 30) = -30 Divide -3 on both sides
[tex]\frac{-3(-4n+30)}{-3} =\frac{-30}{-3}[/tex] [two negative signs cancel each other out and become positive]
-4n + 30 = 10 Subtract 30 on both sides
-4n + 30 - 30 = 10 - 30
-4n = -20 Divide -4 on both sides to get "n" by itself
[tex]\frac{-4n}{-4}=\frac{-20}{-4}[/tex]
n = 5
PROOF
-3(-4n + 30) = -30 Substitute/plug in 5 into "n"
-3(-4(5) + 30) = -30
-3(-20 + 30) = -30 Simplify what's inside the parentheses [PEMDAS}
-3(10) = -30
-30 = -30